Prognostic Value of Glycated Hemoglobin in Frail Older Diabetic Patients With Hip Fracture - Paterni, Simone; Okoye, Chukwuma; Calabrese, Alessia M.; Niccolai, Filippo; Polini, Antonio; Caraccio, Nadia; Calsolaro, Valeria; Monzani, Fabio (Frontiers in Endocrinology, 2021)
Background. Previous studies have shown increased risk of fracture in older patients with poor or strict glycemic control (glycated hemoglobin, HbA1c, ≥ 8% or < 6-7 % respectively); however, these reports did not investigate the oldest-old population. Comprehensive geriatric assessment (CGA) and a patient-centered approach have been proven to improve the quality of care in the management of Type2 Diabetes Mellitus (T2DM) in the older patients, but data regarding T2DM in patients with fragility fractures are still lacking. Aim. To investigate the prognostic role of HbA1c and frailty level in older diabetic patients admitted for hip fracture. Methods. Prospective observational cohort study conducted on diabetic geriatric patients consecutively hospitalized for hip fracture in the orthogeriatric unit of a tertiary care hospital. Preoperative comprehensive geriatric assessment (CGA) was performed. Using the Clinical Frailty Scale (CFS), diabetic patients were categorized in robust (CFS < 5) and frail (CFS ≥ 5), and further stratified according to HbA1c values [Tertile 1 (T1) HbA1c < 48 mmol/mol, Tertile 2 (T2) 48-58 mmol/mol and Tertile 3 (T3) > 58 mmol/mol). Comparisons between continuous variables were performed with analysis of non-parametric test for independent samples, while relationships between categorical variables were assessed by chi-square test. Results. Among the 1319 older patients (mean age 82.8±7.5 years, 75.9% females) hospitalized for hip fracture, 204 (15.5%) had a previous diagnosis of T2DM. T2DM patients showed an increased proportion of multiple concurrent fractures occurred during the accidental fall or syncope (12.7% vs 11.2%, p=0.02). One-year mortality after hip fracture surgery was significantly higher in T2DM as compared to not diabetic patients (21.2% vs 12.5%, p<0.001). No significant difference in mortality was found across HbA1c tertiles; however, frail diabetic patients in the second and third HbA1c tertiles showed higher mortality risk compared to the robust counterparts (26.9% vs 5%, p=0.001 for T2 and 43.5% vs 13.3%, p=<0.05 for T3), while no difference was observed among those in T1. Conclusions: Frail patients with HbA1c ≥ 48 mmol/L showed an increased mortality risk as compared to robust counterparts. CFS represents an important tool to select diabetic subjects with higher likelihood of adverse outcome.